Impact of Economic Factors on Decision Making Power of Rural Nepalese Women Entrepreneurs - Bhattarai, Lekha Nath; Paudel, Deepak Raj (Economic Journal of Nepal, 2014)
This study examines various economic factors that affect the decision making power ofwomen entrepreneurs who were supported by MEDEP/UNDP in rural setting of Parbatdistrict of Nepal. The several components of decision making included are: decision onmaking family relationship, visiting relatives, using family planning tools, householdpurchases, taking loan, using loan, children’s education, owns health checkup andtreatments and government’s official matters. The multistage sampling has been adoptedwith a sample size of 184 women entrepreneurs. Logistic regression analysis revealed thateconomic factors are one of the most vital factors to impact the decision making power ofwomen. Among all the economic factors, women’s occupational status and the person whoowned the house/land factors appeared to be strongly influencing factors than others.Furthermore, selected socio-demographic characteristics were also found to have significantinfluence on the decision making power of women.The Economic Journal of Nepal, Vol. 34, No. 4, October-December 2011 (Issue N0. 136)